Carbon dots based multicolor fluorescence sensor for ratiometric and colorimetric dual-model detection of Cu2+. (July 2022) - Huang, Gengli; Luo, Xueli; Lin, Wanmei; Tang, Wenzhi; Yue, Tianli; Wang, Jianlong; Li, Zhonghong
Abstract: Herein, a multicolor fluorescence sensor with two emission peaks at 445 nm (F445 ) and 560 nm (F560 ) under excitation wavelength of 365 nm was facilely fabricated by hybridizing blue and yellow fluorescence carbon dots (B-CDs and Y-CDs). Cu 2+ could selectively coordinate with the aromatic amino groups of the Y-CDs, thus forming the Cu 2+ -Y-CDs complex through electron pair sharing to efficiently quench the fluorescence of B-CDs by Förster resonance energy transfer. Meanwhile, the complex could suppress photoinduced electron transfer thus enhancing the fluorescence of Y-CDs. The unique interrelated opposite responses of the sensor toward Cu 2+ could generate a remarkable change in the value of F560 /F445 and consequently give rise to more easily distinguishable fluorescent color tonality changes from blue to yellow for colorimetric detection. The sensor possessed a low detection limit of 44.05 nmol L −1 and 169.46 nmol L −1 to recognize Cu 2+ by the ratiometric fluorescent and colorimetric detection, respectively. Recoveries of 96.8–105.9% (RSD <3.8%) and 94.4–108.5% (RSD <7.7%) were respectively obtained in spiked samples by the ratiometric fluorescent and colorimetric detection, indicating their promising potentials to quick pre-warning of Cu 2+ for ensuring food safety and improving public health. Highlights: Dual emission sensor was gained by hybridized two CDs for opposite response for Cu 2+ . Cu 2+ reacted with –NH2 of Y-CDs by electron pair sharing to form Cu 2+ -NH2 complex. The complex inhibited the occurrence of PET to enhance the fluorescence of Y-CDs. FRET derived from B-CDs to the complex to quench the fluorescence of B-CDs. Smartphone was integrated with 3D-printed and sensors for colorimetric detecting Cu 2+ .